Validation of UV-Visible Spectrophotometry for Measuring Rhodamine B Content in Crackers - Silva Oktriana; Suci Rizki Nurul Aeni; Ira Prima Sari (Journal of Applied Food and Nutrition, 2021)
Rhodamine B is a synthetic dye that is often misused as a food coloring in crackers. Rhodamine B consumption through food can irritate the digestive tract, impair liver function, and cancer. The purpose of the study was to determine the content of rhodamine B in crackers. This study used a quantitative method, and purposive sampling was employed as a sampling technique. Method validation was carried out against a UV-Visible spectrophotometer in testing Rhodamine B in crackers. Validation of the method produces a linear regression equation of y = 0.2901x + 0.0082, with a correlation coefficient value (r2) = 0.9985, and a Vxo value of 2.65%. The instrument validation shows a Limit of Detection (LOD) of 0.1582 ppm and a Limit of Quantification (LOQ) of 0.5274 ppm. The results from the accuracy-test showed an average %diff of 0.88%; 3.79%, and -6.88%, while the average percentages of recovery were 101%, 104, and 93% respectively. Precision testing results showed that the value of % RSD 2/3 CV Horwitz. Qualitative measurements showed that all samples tested for Rhodamine B in this study showed negative results. This study suggested that UV-Visible spectrophotometry is a valid method that can be used to measure levels of Rhodamine B in food.